THE IMPACT OF LEADERSHIP DEVELOPMENT DIMENSIONS ON JOB SATISFACTION AND JOB PERFORMANCE: EVIDENCE FROM PRIVATE HIGHER EDUCATION INSTITUTIONS IN CAMBODIA - Som, Muny; Tan, Saroeun; Norng, Sokha (jfpublisher, 2024)
As the business landscape undergoes rapid transformation, leadership development has become an indispensable strategic priority for organizations seeking to maintain their competitive edge. Besides the impact of leader development on employee performance, little is known about its effect through a mediating variable, especially at the higher education level. Therefore, this study attempts to analyze the impact of leadership development on job performance through job satisfaction. The study used a survey questionnaire to collect data from 385 participants who were currently working at higher education institutions in Phnom Penh City. After running a structural equation modeling, the study found that coaching, training and development, and empowerment significantly affect job satisfaction, while participation and delegation do not. Moreover, the study found that training and development and empowerment significantly impact performance, while coaching and delegation do not. Nevertheless, participation has a negative and significant impact on job performance. Finally, job satisfaction has a positive and significant impact on job performance.